If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 120 = 300 Reorder the terms: 120 + 2x = 300 Solving 120 + 2x = 300 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-120' to each side of the equation. 120 + -120 + 2x = 300 + -120 Combine like terms: 120 + -120 = 0 0 + 2x = 300 + -120 2x = 300 + -120 Combine like terms: 300 + -120 = 180 2x = 180 Divide each side by '2'. x = 90 Simplifying x = 90
| 600=15x+5y | | 5=(170-50)/(20-x) | | 8=-2(3p-3)+2(1+2p) | | -90x+-45=45x+45 | | 6=(170-50)/(20-x) | | -14x-5=65 | | 2=8-6 | | -24=2(n+3)-2(3-3n) | | -10x-2=38 | | 2x+80=250 | | -3(x-2)+3(1+2x)=0 | | -2(m+7)=-2 | | 2(3+3n)-2(1+2n)=4 | | 3(2x-8)-10=2(x+1) | | e^2x+7=11 | | -2(2+2n)+3(n-1)=-6 | | -28=2(1+3n)-(3-3n) | | -9x^3y+4x^3y+5xy= | | (4x-20)+(x+12)+(x+1)=59 | | 5=3(-1-x)+2(x+3) | | 6=-3(1+p)+2(3+2p) | | -11+8x=5x+40 | | 25/4-2 | | (-1y+5x)5= | | 16=2(n-3)+2(2n+2) | | -3(3+x)+2(3x+1)=2 | | -39=3(-3m-3)-m | | 2x+(48-9c)-c=-2 | | 3x+3(2x+3)=36 | | -16t^2+112t+288= | | 8x+3z=2+3y | | 33=-3(-2+3x) |